Utveckling av nya analysmetoder för HRV vid emotionella filmstimuli - Haglund,Alma; Österman,Agnes (2026)
There is an established relationship between the autonomic nervous system and the variation in time intervals between consecutive heartbeats, known as heart rate variability (HRV). High HRV is associated with a flexible nervous system, while low HRV has been linked to stress and anxiety. In this study, 32 participants were exposed to four film clips (total duration of 50 minutes), two with negative emotional valence (murder and rape) and two neutral. Electrocardiogram data were recorded to investigate the relationship between physiological responses and emotional stimuli. Conventional methods typically involve extracting and summing a high-frequency band (HF-power), which reflects parasympathetic activity. Lower HF-power is associated with reduced parasympathetic activity and may indicate an increased stress response. Although, current methods are often robust, require longer recording periods and are not entirely reliable. Therefore, a new method was developed in this study, focusing on the maximal intensity within the high-frequency band over time. Three analytical approaches were then applied: changes across the entire exposure period, changes within each film clip, and a ratio-based comparison before and during the most intense segment. The results showed that 57,69 % of participants exhibited a decrease in HF-power over the entire exposure period. During the rape scene, HF-power decreased in 69,23 % of the participants, and 38,46 % in the murder scene. The ratio-based analysis further highlighted differences between stimuli. The results indicate that the proposed method captures decreases in parasympathetic activity more clearly than current methods and shows potential for detecting rapid changes in HRV. Reduced parasympathetic activity was observed during emotional film stimuli. However, further improvements are required for future analyses.
Keywords: Hjärtfrekvensvariabilitet; HRV